Precarity, Cognitive (Non-)Resistance and the Conservative Working Class in China. Issue 4 (8th August 2019) - Lin, Jake
ABSTRACT: Workers' resistance is crucial to understanding how the working class respond to the growing labour precarity in post-socialist China. The labour studies literature posits that inequality and volatile capital movements increase workers' precarity and lead to stronger labour resistance, such as strikes. However, workers' cognition as an integral part of resistance has been rarely studied. This article examines cognitive resistance by Chinese workers from different tier cities by looking at their social trust, class identity, understanding of policies and class solidarity. Despite capital movements and precarity causing more labour unrest, it does not necessarily lead to a stronger cognitive resistance. While inequality and precarity are greater in the more developed megacities with a shifting capital favourability, workers in megacities display a more conservative cognitive resistance than those from the lower-tier cities. This study of workers' cognitive resistance provides insight into the future of the Chinese labour movement. It argues that the working class's current cognitive non-resistance suggests that even if a window of opportunity were to appear in the wall of state oppression, workers are not cognitively prepared to coalesce into a coherent social movement that would bring about transformative changes.